(untitled) (Journal of history, 2019)
Тhe article discusses the theoretical and methodological issues of the historical continuity of statehood of the states of Deshti-i-Kipchak. Political unions formed in the steppes were characterized by a different form of statehood, with features of development, primarily elements of historical continuity. In other words, the methods of organization and government that have taken place here are often inherited from their near and distant predecessors. In this regard, it is necessary to talk about the important role of continuity in nomadic statehood.The modern movement of historical knowledge requires further understanding of the process of continuity of state institutions of the Kazakh Khanate, which was a direct continuation of the Turkic state traditions, the political and ideological successor of the Golden Horde, Ak Horde, Mogulistan, Nogai Horde, Abulkhair Khanate and an understanding of the essence of the changes that were directly related to transformation of the internal mechanisms of a nomadic society.